Neutron emission spectroscopy measurements with a compact liquid scintillation detector for NBI-heated plasma at EAST. (16th July 2018) - Ge, L J; Hu, Z M; Zhang, Y M; Sun, J Q; Yuan, X; Peng, X Y; Chen, Z J; Du, T F; Gorini, G; Nocente, M; Tardocchi, M; Hu, L Q; et al.
Abstract: Neutron emission spectroscopy (NES) measurement aimed at providing the information on fast ions induced by auxiliary heating systems at Experimental Advanced Superconducting Tokamak (EAST), with a liquid scintillation detector is described. It is the first time that the NES diagnostics are employed to probe fast ions induced by neutral beam injection (NBI) at EAST. The time trace of the fusion neutrons, obtained by the liquid scintillation detector, was consistent with the result measured by a standard 235 U fission chamber under NBI heating scenario, which verifies the performance of the detector. NUBEAM code is used to determine the fast deuteron velocity distribution using the parametrized plasma profiles as input. The pulse height spectrum of the fusion neutrons was successfully reproduced by combining the simulation of the neutron energy spectrum and the calculation of the detector response functions. The experimental data are also interpreted from a view of weight functions, which illustrate the velocity-space sensitivity of the liquid scintillation detector with a radial line of sight. The results demonstrate the capability of the liquid scintillation detector to contribute to studies on fast-ion physics at EAST.